Compact Anthology of World Literature - Getty, Laura; Kwon, Kyounghye (Open textbook library., 2016)
A world literature class may be the first place that some students have encountered European works, let alone non-Western texts. The emphasis in this anthology, therefore, is on non-Western and European works, with only the British authors who were the most influential to European and non-Western authors (such as Shakespeare, whose works have influenced authors around the world to the present day). In a world literature class, there is no way that a student can be equally familiar with all of the societies, contexts, time periods, cultures, religions, and languages that they will encounter; even though the works presented here are translated, students will face issues such as unfamiliar names and parts of the story (such as puns) that may not translate well or at all. Since these stories are rooted in their cultures and time periods, it is necessary to know the basic context of each work to understand the expectations of the original audience. The introductions in this anthology are meant to be just that: a basic overview of what students need to know before they begin reading, with topics that students can research further. An open access literature textbook cannot be a history book at the same time, but history is the great companion of literature: The more history students know, the easier it is for them to interpret literature. These works can help students understand the present, as well. In an electronic age, with this text available to anyone with computer access around the world, it has never been more necessary to recognize and understand differences among nationalities and cultures. The literature in this anthology is foundational, in the sense that these works influenced the authors who followed them. A word to the instructor: The texts have been chosen with the idea that they can be compared and contrasted, using common themes. Rather than numerous (and therefore often random) choices of texts from various periods, these selected works are meant to make both teaching and learning easier. While cultural expectations are not universal, many of the themes found in these works are.